Latent toxoplasmosis, Cytomegalovirus, and Herpes Simplex Virus infections and risk of motorcycle accidents: A case-control study in a county with a high rate of motorcycle injuries in Iran - Rayatdoost, Esmail; Chegin, Mahdi; Taghipour, Ali; Shadmand, Enayat; Rezaei, Fatemeh; Falahi, Shahab; Kenarkoohi, Azra; Badri, Milad; Solhjoo, Kavous; Abdoli, Amir (PloS one, 2024)
Road traffic injuries (RTIs) are among the most important issues worldwide. Several studies reported that infection with the neurotropic parasite Toxoplasma gondii (T. gondii) increased the risk of car accidents. In this study, our objective was to investigate the possible associations among latent T. gondii, Cytomegalovirus (CMV), and Herpes Simplex Virus (HSV) infections with the risk of motorcycle accidents in Jahrom (Fars Province), which is a county with a high rate of motorcycle accidents in Iran. In the setting of a case-control study; 176 motorcyclist men, including 88 survivors of motorcycle accidents and 88 motorcyclist without accidents, were considered as case and control groups, respectively. Rates of latent infections with T. gondii, CMV, and HSV were assessed by an enzyme-linked immunosorbent assay (ELISA). Eleven of 88 (12.5%) in the case group and 22 of 88 (25.0%) in controls were positive for anti-T. gondii IgG antibodies, this difference was statistically significant (OR = 0.42; CI: 0.19-0.95, p = 0.03). The general seroprevalence of CMV (94.3% in the case group vs. 87.5% in the control group, OR = 2.37; CI: 0.78-7.13, p = 0.12) and HSV (63.6% in the case group vs. 62.5% in the control group, OR = 1.05; CI: 0.57-1.94, p = 0.87) were not significantly different between the case and control groups. Although latent toxoplasmosis has been associated with traffic accidents in recent reports, we found a negative association between latent toxoplasmosis and motorcycle accidents among survivors of these accidents. As such, latent CMV and HSV infections did not differ significantly between the cases compared to the control groups.